Microfinance and gender inequality: cross-country evidence. Issue 20 (28th November 2017) - Zhang, Quanda; Posso, Alberto
ABSTRACT: Microfinance enables poor women to engage in income-generating activities, which helps them become financially independent, strengthening their decision-making power within the household and society. Consequently, microfinance has the potential to reduce gender inequality (GI). Case-study evidence from across the developing world both supports and contradicts this hypothesis. We therefore revisit this issue using macroeconomic cross-country panel data for 64 developing economies over the period 2003–2014. We find that women's participation in microfinance is associated with a reduction in GI. However, regional interactions reveal that cultural factors are likely to influence the GI–microfinance nexus.